Rumble fish - Hinton, Susan Eloise (Dell, 1976)
A junior high school boy idolizes his older brother, the coolest, toughest guy in the neighborhood, and wants to be just like him.
Keywords: Brothers and sisters / Fiction; Social problems / Fiction; City and town life / Fiction; Bruder; Geltungsbedürfnis; Männliche Jugend; Vorbild; Jugendbuch